2012
DOI: 10.1209/0295-5075/99/28001
|View full text |Cite
|
Sign up to set email alerts
|

A note on grain topology-size relationship of three-dimensional polycrystalline microstructures

Abstract: PACS 81.10.Aj -Theory and models of crystal growth; physics and chemistry of crystal growth, crystal morphology, and orientation PACS 64.30.Ef -Equations of state of pure metals and alloys Abstract -A grain topology-size equation for three-dimensional grains is suggested by considering the interactions of the nearest-neighbor grains, which indicates that the average grain size of a given topological class is determined by the difference between the grain face number and the average face number of nearest neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The results revealed that a strong correlation exist between grains and their first nearest neighbors, while there exist very little (negligible) correlation between grains and their kth (k2) nearest neighbors (on average). This confirms that the topological correlations of 3D grains with their kth layers (k2) of nearest-neighbors may have trivial effect on the topologysize relationship, and thus provides support to a new grain topology-size equation [17] that only considered the nonrandom first nearest-neighbor interactions.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The results revealed that a strong correlation exist between grains and their first nearest neighbors, while there exist very little (negligible) correlation between grains and their kth (k2) nearest neighbors (on average). This confirms that the topological correlations of 3D grains with their kth layers (k2) of nearest-neighbors may have trivial effect on the topologysize relationship, and thus provides support to a new grain topology-size equation [17] that only considered the nonrandom first nearest-neighbor interactions.…”
Section: Discussionsupporting
confidence: 65%
“…(4) takes the form of eq. (1), the proposed grain topology-size equation in [17]; which can serve as a special case of this general grain topology-size equation (eq. (4)).…”
Section: Methods and Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…We also experimentally analyzed the topological characteristics of 3D grain microstructures generated by Monte Carlo-Potts simulation [12][13][14]. A continuum microstructure was mapped onto a cubic lattice with 300 × 300 × 300 sites and with periodic boundary conditions in three directions (see details of the method in our previous papers [1,2,15,16]). 6093 grains at different simulation time were sampled.…”
mentioning
confidence: 99%
“…-Grains structures, biological tissues and common soap froths bear a similar nature in that they are space-filling celluar structures [1,2]. Topological properties of such cellular structures are subjects of longstanding interest which despite intensive studies is still not fully understood [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Among several topological relations summarized in the past (including Aboav-Weaire law on nearest-neighbor correlations [3,4], the von Neumann law on the growth rate of individual cells [1,5], the Lewis law on the statistics of cell area [6], and the scaling law on the probability distribution of the cells [7]), the Aboav-Weaire law [3,4] is a fundamentally empirical expression to describe the short-range topological correlations between a center grain and its first nearest neighbors in two dimensions.…”
mentioning
confidence: 99%